Effectiveness of 10% povidone-iodine drying time before Peripheral Intravascular Catheter insertion: preliminary results from an explorative quasi-experimental study - Alvisa Palese; Federica Cescon (Universidade de São Paulo, 2013)
AIM: to investigate the effectiveness of 10% povidone-iodine after a 30-second or 2-minute drying time on microbial count reduction at the point of a Peripheral Intravascular Catheter (PIC) insertion. A quasi-experimental design was adopted. In total, 53 patients were enrolled, 25 were exposed to a 2-m drying time and 28 to a 30-s drying time. From the preliminary results of this study, no differences in the occurrence of contamination have emerged between patients receiving 30-s and 2-m drying time for 10% povidone-iodine solutions.